Devayan Language Translator Dictionary Application Using the Levenshtein Distance Method on Android - Faturrahman, Puja; Ardian, Zalfie; Maryana, Maryana (Journal of Advanced Computer Knowledge and Algorithms, 2025)
Indonesia is a country with a rich diversity of regional languages. Language is the primary tool of human communication, serving as a means to establish social relationships in daily life and as a medium for conveying information. One of the regional languages in Indonesia is Devayan, the native language of the people in Simeulue Regency. This language is used as a daily communication medium by the local residents. As one of Indonesia's archipelagic regions, Simeulue Island has various tourism potentials that attract tourists, workers, and students from outside the region. However, communication barriers often occur when visitors to Simeulue Island face difficulties interacting with the local community. Additionally, the language is gradually fading with the passage of time, as many young generations on Simeulue Island now have limited understanding of their regional language. Therefore, a dictionary application is needed to translate vocabulary from Devayan to Indonesian and vice versa. The Levenshtein Distance method is applied to the application's search feature, which has proven capable of correcting errors in input words and suggesting the closest words to users with an accuracy rate of 80.95%.